Metonymy, the Origins of Expression and the Trends of Contrast - Yacoub, Jalila (International Journal of Culture and History, 2024)
This paper is concerned with metonymy in the rhetorical works of the ancient Arabs, and what is meant by it according to the context of pronunciation and reception with the stylistic and pragmatic concepts, and inferring them from imagination, methodology, and indication, linking that to time, reality and pattern of thinking; however, the problem that we raise in this research is the extent to which today's generations are able to understand this books, and is it something that benefits the learners and matches their era, or is it for them a burden that they have no ability to understand or interpret? A problem that we address from two dimensions: the first is cognitive and referential, the second is methodological in the relationship of transmission with the mind, and codification with thinking and management; difficulties in learning and teaching did not go beyond the circle of speakers of their own language, so how about speakers of another language? We have limited our discussion of the issue to its first level, and we wanted to explain part of it in two aspects: the first is educational related to curricula and methods of approximating knowledge, the second is social and psychological that makes language a tool and not an end, but at the same time it does not negate its originality and specificity.